COVID-19 and geographical area of origin. (April 2021) - Norman, Francesca F.; Crespillo-Andújar, Clara; Pérez-Molina, José Antonio; Comeche, Belén; Chamorro, Sandra; Monge-Maillo, Begoña; Moreno-Guillén, Santiago; López-Vélez, Rogelio; ,; Vizcarra, Pilar; Norman, Francesca; Crespillo, Clara; et al.
Abstract: Objectives: To describe and compare the main clinical characteristics and outcome measures in hospitalized patients with confirmed coronavirus disease 2019 (COVID-19) according to geographical area of origin. Methods: A retrospective analysis of patients hospitalized with confirmed COVID-19 at a referral centre in Madrid, Spain, during March–May 2020 was performed. Recorded variables (age, gender, intensive care unit (ICU) admission, outcome), and geographical area of origin were compared for Europeans and non-Europeans (Latin Americans, Asians and Africans). Results: In total, 2345 patients with confirmed COVID-19 hospitalized during the study period were included in the study. Of these, 1956 (83.4%) were European and 389 (16.6%) were non-European (of whom over 90%, 354/389, were Latin American). Non-Europeans were significantly younger than Europeans (mean 54 (SD 13.5) versus 70.4 (SD 15.1) years, p < 0.001); the majority were male (1420/2345, 60.6%), with no significant differences in gender between Europeans and non-Europeans (1197/1956 (61.2%) male in the European group versus 223/389 (57.3%) male in the non-European group, p 0.15). In-hospital mortality overall was higher in Europeans (443/1956, 22.7%) than in non-Europeans (40/389, 10.3%) (p < 0.001), but there were no significant differences when adjusted for age/gender (OR 1.27, 95% CI 0.86–1.88). Non-Europeans were more frequently admitted to ICU (71/389, 18.3%) compared with Europeans (187/1956, 9.6%) (p < 0.001) and a difference in ICU admission rate was also found when adjusted for age/gender (OR 1.43, 95% CI 1.03–1.98). Conclusions: No significant differences in mortality were observed between Europeans and non-Europeans (mainly Latin Americans), but an increase in ICU admission rate was found in non-Europeans.